FUZZY LOGIC APPLICATION FOR DETERMINING THE FEASIBILITY OF NICKEL MINING IN SOUTHEAST SULAWESI PROVINCE - Ni Luh Ika Tri Agustina; Agus Maman Abadi (Barekeng)
This study uses the Mamdani method to assess the feasibility of nickel mining locations in Southeast Sulawesi Province. Despite the crucial role of mining in the Indonesian economy, research on the site feasibility decisions in mining using the Mamdani method still needs to be completed. Therefore, this study addresses this knowledge gap by providing new contributions and effective solutions. The Mamdani method is employed in the various stages of mining activities, particularly in feasibility studies, which are the main focus. Mining feasibility studies involve both technical and non-technical analyses, encompassing aspects such as nickel reserves and environmental impacts. This research seeks to expand the use of the Mamdani method in mining site feasibility decisions, offering sustainable and environmentally responsible solutions. The research results show that North Konawe Regency has very large estimated nickel reserves but has a relatively low environmental impact and is quite far from the port, thus achieving a high location suitability score for mining. On the other hand, Konawe Regency has lower nickel reserves but has quite a large environmental impact, and the distance to the port is quite far, so the location feasibility score is lower.  The outcomes of this research are expected to provide new insights, fill knowledge gaps, and serve as a valuable reference for future mining site feasibility decision-making. The translation is accurate, well-structured, and free from plagiarism.